STRATEGI MEDIA RELATIONS HUMAS PT. PELABUHAN INDONESIA III DALAM HANDLING CRISIS PEMBERITAAN - Agesty Sabreyna RM; R. Bambang Moertijoso (Jurnal Komunikasi, 2015)
Media Relations was a requirement for Public Relation practitioners thatPR had an important role in a relationship with media. It was because thetask of public relation was the mass media and journalist. PT PelabuhanIndonesia III (Persero) as a State-owned enterprised cannot separate withthe crisis news. The strategy of media relations was very important to handlethe negative publicity because it could affect a company’s image.This research used qualitative descriptive method with data collectiontechniques, observation, interviews, and literature. The aim was determinethe media relations strategy of PT. Pelabuhan Indonesia III (Persero) tohandle media crisis and compared it with the theory used. This study usedtheory of public relations, crisis and the media of media relations in crisissituation. The crisis of media should solve quickly and precisely, by handling the crisis.The results of this research to handle a news crisis, the steps were: 1). Analysis,2). Identification, 3). Responds media. All the four steps above, the activity ofmedia relations were very important to do, and the strategy of media relationsused to support roles, functions and duties of public relations. The strategy ofmedia relations were: By served the media, By established a reputations for reliability, By supplying good copy, By cooperations in providing materials, verifications By provided facilities, and By build a personal relationship withthe media. The six of those strategies was the activity of public relationscommunications to establish understanding and good relations with the massmedia.Keywords: Crisis, Public Relations, Media Relations, Strategy, andPelabuhan Indonesia III (Persero)